KETERBUKAAN INFORMASI (FULL DISCLOSURE) PERUSAHAAN PUBLIK DI SEKTOR INDUSTRI PERTAMBANGAN BATUBARA PT BUMI RESOURCE, Tbk. DALAM MENJAGA LIKUIDITAS SAHAM (STOCK LIQUIDITY) - Santoso, Budi; Damayanti, Novita; Razak, Razie (Jurnal Publisitas, 2019)
A fundamental characteristic of investor relations is the full disclosure of information for the companies that have gone public through the capital market and have the title "Tbk”. To public, a company that has declared going public, having the responsibility to disclose any information regarding the activities or internal actions of the company to all stakeholders, especially to its investors, counting when a public company is experiencing an internal crisis. The purpose of this study was to determine the use of communication tools in order to carry out public information disclosure by public companies (issuers) in maintaining stock liquidity. The study was conducted at the office of PT Bumi Resources, Tbk., 12th floor Bakrie Tower Jalan Epicentrum Utama Raya, Rasuna Epicentrum Kuningan, South Jakarta. The type of research used is descriptive with a qualitative approach. Techniques used in data collection include: a) Primary data in the form of in-depth interviews with key informants and data from the company, and b) Secondary Data obtained through literature such as books, journals, articles, and previous research related to this research. Communication tools carried out by the investor relations division consist of; Press release, News, Annual Report, Analyst Meeting, GMS, Website, Contact Center, Financial Reports, Financial Media Meeting and Financial Advertising. The use of these tools depends on the situation and conditions faced by the company.